Diseño y simulación de una antena plana alimentada con una linea microstrip en la banda de ondas milimétricas para 5g - Cisneros Quishpe, Sheyla Estefania (2022)
Actual technology development for all life environments and specially around telecommunications field is coming with new applications and new devices that offer to the user to interact with this new era of technology day by day; every time are more common terms or words related to the Internet of Things (IoT), artificial intelligence and communication systems based on 5G networks, for this fulfillment, an special element part of all of these new devices are the antennas, which must be adapted for higher speed on reception and transmition and support even more data flow information; therefore, this project plans a planar antenna design and simulation with microstrip line feeder allowing its operation among milimetric waves 5G frequency ranges. Proposed antenna has been simulated using CST Studio Suite Simulation Software, antenna operates at 45 GHz frequency, the structure has been designed over substrate with εr=2,2, based on previous studies about patch antennas and with several arrays types, besides taking in account the use of approach microstrip line feeding. This document includes 5 chapters. The first one explains the problems, and general and specific objectives to be reached. In second chapter is realized a state of the art study. Beyond third chapter, it is detailed procedure used for designing and simulation for the structure. Inside fourth chapter is exposed all results and operation of the antenna designed. Finally, in fifth chapter are defined conclusions and recommends that have been thrown out from this investigation project.